DESKRIPSI FAKTOR-FAKTOR PADA KONSUMEN MEMBELI KEBUTUHAN BAHAN POKOK DI PASAR TRADISIONAL DAN PASAR MODERN (STUDI KASUS PASAR TRADISIONAL PINASUNGKULAN DAN SWALAYAN FRESHMART BAHU KOTA MANADO) (Description the factors on consumer buying staple goods in traditional market and modern markets in the Manado City (Case study of Pinasungkulan Traditional Market and Modern Market Freshmart Bahu in Manado City)) - Julian Yosua Mokalu; Audrey M. Maweikere; Nordy F. L. Waney (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This objective of this research is to describe the factors that influence consumers in the decision to buy staple goods in traditional or modern markets in the city of Manado. The data sources used in this research are primary data and secondary data. Primary data obtained from direct interviews with respondents using a list of questions. Secondary data were obtained from the BPS office or the Manado City Central Statistics Agency. Determination of the sample using the Accidental Sampling method. Respondents who were used as research samples were determined incidentally, when the researcher met respondents who were willing to be interviewed at the research location. Respondents who are used as research samples are consumers who have bought basic commodities and are willing to be interviewed at the research location. The sample was determined as many as 40 respondents, namely: 20 respondents in the traditional market Pinasungkulan and 20 respondents at the supermarket Freshmart Manado. The internal factors (consumer characteristics) namely age, education, occupation, income, number of dependents, and basic necessities purchased showed that consumers feel better, comfortable and can meet all the basic necessities they buy. both in traditional and modern markets. External factors from market conditions Â showed that respondents shop more in modern markets because it is guaranteed, quality, service, and price as well as a location that is easy to reach and access by consumers, and psychological factors where consumers feel comfortable in the modern market with 12 respondents and a percentage of 30%.Keywords: Consumen ,Basic Material Needs, Traditional Markets, Modern Markets